ANALYSIS OF PROCEEDINGS OF LAST FIVE YEARS OF THE FIEP CONGRESS – From 2011 to 2015 (Fiep Bulletin - online, 2016)
The International FIEP Congress has been held in Foz do Iguaçu for 31 years. Its organization presents works of different shapes and areas. Including great concern about aspects of health and especially of Physical Education. Through the annals of this Congress we can see the change in service training areas, sometimes for graduation, sometimes to the bachelor's degree. Because of this, it is of utmost importance to evaluate and analyze the proceedings of this conference to identify the study options for researchers / authors participating in this congress. This work aims to analyze the annals of Congress FIEP from 2011 to 2015, categorizing the works by knowledge areas, and identifying the most studied ones. For the purpose of this paper, results were presented relating to the work published in the journals Article I, Article II and summaries of the years 2011 to 2015. All works were selected and analyzed from your resume in Portuguese. The categorization used to check knowledge area was established by CAPES, namely: Exact Sciences, Engineering, Health Sciences, Agricultural Sciences, Social Sciences, Humanities, Life Sciences, Linguistics, Literature and Arts. The results show that each year there have been changes related to the amount of work and the percentage of work referring to Physical Education in relation to other areas. We conclude that The Congress, through publications, presents a wide range of different areas of work. Specifically in relation to Physical Education, there are 517 works related to graduation and 1,406 to  bachelor's degree. Identifying the event as a special area of research focused on the bachelor's degree in Physical Education.
Keywords: scientific production; research; formation